The antioxidant activity and genotoxicity of isogarcinol. (1st July 2018) - Liu, Zijin; Li, Gang; Long, Cheng; Xu, Jing; Cen, Juren; Yang, Xiaobo
Highlights: Isogarcinol had strong antioxidant activity. Isogarcinol did not have a genotoxic effect on HepG2 cells in the range of concentrations tested. Isogarcinol protected HepG2 cells from H2 O2 -induced oxidative stress by reducing ROS generation and blocking the ROS-induced mitochondrial apoptosis pathway in HepG2 cells. Abstract: The antioxidant activity and genotoxicity of isogarcinol were assessed by several in vitro tests. Its IC50 values for DPPH and ABTS were 36.3 ± 3.35 µM and 16.6 ± 3.98 µM, respectively, which were all lower than those of VC and BHT. Isogarcinol had no cyctotoxic or promotional activities at 1–10 µM in the CCK-8 assay, and negligible genotoxic effects at 50–500 µM on HepG2 cells by the single-cell gel electrophoresis assay. Pre-incubation of the cells with 0.5–1.5 µM isogarcinol, before exposure to H2 O2, significantly increased cell viability in a concentration-dependent manner. Isogarcinol also reduced intercellular reactive oxygen species accumulation, lactate dehydrogenase release and malondialdehyde levels, and increased superoxide dismutase activity and glutathione levels. Western-blot analysis revealed that it up-regulated pro-caspase-3 and reduced cleaved caspase-3 during H2 O2 -induced oxidative stress. All the above results indicate that isogarcinol promises to be useful as a natural antioxidant.